2019
DOI: 10.3389/fphys.2019.00370
|View full text |Cite
|
Sign up to set email alerts
|

HECT E3 Ligases: A Tale With Multiple Facets

Abstract: Ubiquitination plays a pivotal role in several cellular processes and is critical for protein degradation and signaling. E3 ubiquitin ligases are the matchmakers in the ubiquitination cascade, responsible for substrate recognition. In order to achieve selectivity and specificity on their substrates, HECT E3 enzymes are tightly regulated and exert their function in a spatially and temporally controlled fashion in the cells. These characteristics made HECT E3s intriguing targets in drug discovery in the context … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
88
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 120 publications
(88 citation statements)
references
References 96 publications
0
88
0
Order By: Relevance
“…With new research and discoveries becoming available, there is mounting evidence that the lesser known HECT E3 ubiquitin ligases play critical roles in regulating intracellular processes and their dysfunction have been suggested to contribute to the onset of many diseases and disorders [4,[29][30][31][32]. Here we discuss the latest discoveries on these lesser known members of the HECT E3 ubiquitin ligases and on their emerging roles in developmental and neurological abnormalities, cancers, and embryogenesis.…”
Section: The "Other" Hect E3 Ubiquitin Ligases: Important Players Inmentioning
confidence: 97%
“…With new research and discoveries becoming available, there is mounting evidence that the lesser known HECT E3 ubiquitin ligases play critical roles in regulating intracellular processes and their dysfunction have been suggested to contribute to the onset of many diseases and disorders [4,[29][30][31][32]. Here we discuss the latest discoveries on these lesser known members of the HECT E3 ubiquitin ligases and on their emerging roles in developmental and neurological abnormalities, cancers, and embryogenesis.…”
Section: The "Other" Hect E3 Ubiquitin Ligases: Important Players Inmentioning
confidence: 97%
“…The human proteome encodes more than 600 E3 ligases that fall into three main groups: the really interesting new gene (RING) class comprising ∼600 members, the homologous to E6AP C terminus (HECT) class which includes at least 28 members and the RING between RING (RBR) class encompassing 14 members [59][60][61]. A detailed ubiquitin taxonomy, specifically, a precise mapping of the enzyme to substrate, is currently lacking, however, the sheer number of ligases points strongly a high degree of specificity.…”
Section: Targeting E3 Ligasesmentioning
confidence: 99%
“…The cullin-RING ligase (CRL) is a kind of multi-subunit RING E3 ligase that can be further divided into the S phase kinase associated protein 1 (SKP1)/cullin 1 (CUL1)/F-box protein complex (SCF), CUL2-elongin B/C-VHL or SOCS proteins (CRL2), CUL3-BTBs, CUL4-DDB1-DCAFs (CRL4), CUL5-elonginB/C-SOCS proteins, and the CUL7/F-box/WD repeat-containing 8 (FBXW8) subfamily of E3 ligases (20,21). HECTs, the second largest E3 ligase family in humans, comprises 28 members and can be categorized into three subfamilies: Neural precursor cell expressed developmentally downregulated protein (NEDD)4 family, HECT domain-containing protein (HERC) family and 'other' HECT ligases (22). Studies to date have suggested that only the NEDD4 family and a member of the Other HECT ligase families are related to GC.…”
Section: Classification Of E3 Ubiquitin Ligasesmentioning
confidence: 99%